PENGHAMBATAN PERTUMBUHAN JAMUR Schizophyllum commune Fries OLEH EKSTRAK ETANOL DAUN KRATOM (Mitragyna speciosa Korth) - Rabani, .; Diba, Farah; Muflihati, . (Universitas Tanjungpura, 2017)
The aim of this research is to evaluate the anti-fungal activity and the effective concentration of Kratom leaf extract in inhibiting the growth of fungus Schizophyllum commune Fries. Kratom leaf was extract with ethanol solution. The concentration of kratom leaf extract used for treatment is 0%, 2%, 4%, 6%, 8% and 10%. Toxicity test was done by food poisoning method on PDA media with Kratom leaf extract. Result of the research showed that Kratom leaf activity extract is categorized low for 2% concentration, medium for concentration 4% and 6%, strong for concentration 8%, and very strong for concentration 10%. Concentration 10% of Kratom leaf is a very strong anti-fungal activity that inhibits 85.50% growth of Schizophyllum commune fungus. However, the optimum concentration of Kratom leaf extract was achieved on concentration 8% which inhibiting the growth of Schizophyllum commune fungi by 76.03%.Keywords: anti-fungal, extract ethanol, Kratom leaf, Mytragina Speciosa Korth, Schizophyllum commune Fries.